The Impact of TikTok Influencers Endorser on Consumer Purchase Intentions for Scarlet Whitening Brand - Kasuma, Achmad Bintang Herida; Rabbani, Rahadian Rashief (CV. Lenggogeni Data Publishing, 2024)
This study examines the impact of TikTok influencers on consumer purchase intentions, focusing on Scarlet Whitening products. Utilizing a quantitative approach, data was collected via survey methods from TikTok users familiar with Scarlet Whitening products. Analysis revealed a significant correlation between TikTok influencers' endorsements and customer purchase intentions, highlighting the influencers' substantial role in shaping consumer behavior. The findings underscore the importance of considering social media influencers in contemporary marketing strategies, particularly for businesses in sectors like cosmetics and beauty. Academically, this study contributes to understanding digital-age consumer behavior, while practically, it offers insights for enhancing marketing plans through strategic influencer collaborations.